Preparation process of coil for miniature inductor
High-precision copper columns are prepared through laser cutting and UV ink treatment technology, and the plating materials are compressed by blue adhesive sheets and filled with through holes, which solves the problem that the micro-inductor coil preparation process in the prior art is difficult to achieve high accuracy and high reliability, and realizes high-efficiency electrical connection and conduction, which is suitable for high-frequency applications.
Patent Information
- Application Number
- CN202411920758.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
AI Technical Summary
The existing micro-inductor coil preparation process is difficult to meet the requirements of high precision, high reliability and low cost at the same time, especially in the preparation of multi-layer structures, such as inaccurate alignment and poor conduction.
Laser cutting and UV ink impregnation development and exposure treatment technology are used to prepare high-precision copper column shapes, and the plating materials are compressed through blue adhesive sheets and filled with through holes to achieve efficient electrical connection and conduction of the coil.
It improves the alignment accuracy and conduction reliability of the micro-inductor coil, enhances the insulation performance and overall performance of the coil, and is suitable for high-frequency application environments.
Smart Images

Figure CN119742174A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of micro-inductors, and in particular to a process for preparing a coil for a micro-inductor. Background Art
[0002] Micro-inductors are widely used in electronic devices, especially in high-frequency circuits and miniaturized products. With the continuous miniaturization and integration of electronic products, the demand for micro-inductors is growing. The existing micro-inductor preparation processes mainly focus on improving production efficiency, reducing costs and ensuring product quality. The development of these technologies has greatly promoted the progress of the electronics industry. However, in practical applications, how to further improve the accuracy and reliability of the preparation process while ensuring performance is still an important issue.
[0003] At present, common methods for preparing micro-inductor coils mainly include traditional winding methods, printed circuit board (PCB) methods, etc. Although the winding method is simple to operate, it has problems such as low automation, low production efficiency, and poor consistency. The printed circuit board method transfers the copper foil pattern to the substrate through steps such as photolithography and etching. This method can achieve higher precision and mass production, but in the preparation process of multi-layer structures, problems such as misalignment and poor conduction are prone to occur. In addition, there are other more advanced preparation methods, such as laser direct writing technology and 3D printing technology. These methods can improve the above problems to a certain extent, but there are still shortcomings such as high cost and complex equipment.
[0004] In the prior art, whether it is the traditional winding method or the printed circuit board method, it is difficult to simultaneously meet the requirements of high precision, high reliability and low cost. In particular, for multi-layer micro-inductors, the existing preparation methods have obvious deficiencies in alignment accuracy and conduction reliability, which limits their wide application in high-performance electronic devices. Therefore, a new preparation process is urgently needed to solve these problems. Summary of the invention
[0005] The purpose of the present application is to overcome the above technical problems. The present application provides a coil preparation process for a micro inductor.
[0006] The present application provides a micro-inductor coil preparation process using the following technical solutions: A process for preparing a coil for a micro-inductor comprises the following steps: S1: Copper foil coating on organic tape; S2: Use laser to cut the required copper pillar shapes on the A and B surfaces; S3: impregnating the A side and the B side with insulating UV ink respectively, and performing development and exposure treatment; S4: Align surface A and surface B and press them together using the blue adhesive sheet; S5: removing the temporary protective film on the A surface and the B surface; S6: forming a through hole penetrating the A side and the B side to achieve electrical connection between the two sides; S7: Fill the through hole with electroplating material to complete the upper and lower conduction of the A and B surfaces.
[0007] By adopting the above technical solutions, high-precision preparation of coils for micro-inductors is achieved. Specifically, by using copper foil coating on organic strips and laser cutting technology, the shape and size of the copper pillars are accurately controlled to ensure that the gap between the copper pillars is 5-15 microns, which improves the stability and consistency of the coil. At the same time, the insulation performance of the coil is effectively enhanced by impregnating the A and B surfaces with insulating UV ink and developing and exposing them. After aligning and pressing the A and B surfaces, the temporary protective film is removed, and by forming a through hole that runs through the two sides and filling it with electroplating materials, efficient electrical connection is achieved, further improving the overall conductivity and reliability of the coil.
[0008] Preferably, the gap between the copper pillars is 5-15 microns.
[0009] By adopting the above technical solution, the gap between the copper pillars is set to 5-15 microns, which can effectively improve the density and integration of the coil and reduce the overall volume of the micro-inductor. At the same time, the design within this gap range is conducive to ensuring good electrical performance and mechanical stability, avoiding short circuits caused by too small gaps or electromagnetic coupling efficiency affected by too large gaps. In addition, this design also facilitates the implementation of subsequent processing steps, such as the formation of through holes and the filling of electroplating materials, thereby ensuring the reliability and consistency of the final product.
[0010] Preferably, the copper column has a thickness of 20-500 microns.
[0011] By adopting the above technical solution, the thickness of the copper pillar is set to 20-500 microns, so that the coil has good electrical performance and mechanical strength. The copper pillar within this thickness range can ensure high current transmission efficiency while reducing resistance loss and improving the overall performance of the inductor. In addition, reasonable thickness design can also effectively control production costs while maintaining good conductivity, making it suitable for large-scale industrial production.
[0012] Preferably, the thickness of the blue adhesive sheet is 10-20 microns.
[0013] By adopting the above technical solution, the thickness of the blue adhesive sheet is controlled within the range of 10-20 microns, which can not only effectively ensure the insulation performance between the copper pillars, but also ensure the stability and reliability of the entire coil structure. At the same time, the adhesive sheet within this thickness range can maintain good mechanical strength during laser cutting and subsequent processing, avoiding processing difficulties and reduced yields caused by being too thin or too thick. In addition, this thickness range can also optimize the overall size of the inductor, improve space utilization, and meet the requirements of miniaturized design.
[0014] Preferably, the copper foil has a thickness of 10-50 microns.
[0015] By adopting the above technical solution, the thickness of the copper foil is controlled within the range of 10-50 microns, which can effectively improve the conductivity and mechanical strength of the coil while ensuring the stability and reliability of the process. This design not only reduces material costs, but also improves the overall performance and service life of the product.
[0016] Preferably, the organic tape is made of polyimide film.
[0017] By adopting the above technical solution and selecting polyimide film as the organic strip material, the heat resistance and mechanical strength of the coil for the micro-inductor can be significantly improved. Polyimide film has excellent high temperature stability, good dielectric properties and chemical stability, and can maintain stable physical and electrical properties in a high temperature environment, thereby ensuring the reliability and durability of the coil during long-term operation. At the same time, polyimide film has good flexibility and is easy to process and shape, which helps to improve production efficiency and yield rate.
[0018] A coil structure for a micro inductor is made using the above-mentioned micro inductor coil preparation process, characterized in that it includes multiple copper pillars and a blue adhesive sheet with a spiral direction, the gap between adjacent copper pillars is 5-15 microns, the thickness of the copper pillars is 20-500 microns, and the thickness of the blue adhesive sheet is 10-20 microns.
[0019] By adopting the above technical solution, the coil structure for the micro inductor can significantly improve the performance and reliability of the inductor. Specifically, the design of the copper pillar and the blue adhesive sheet enables the inductor to have a higher inductance value and better frequency characteristics. At the same time, the gap between adjacent copper pillars is controlled within the range of 5-15 microns, ensuring a good electrical isolation effect. In addition, the thickness of the copper pillar is set between 20-500 microns, which not only ensures sufficient conductivity, but also effectively improves the mechanical strength. The blue adhesive sheet serves as an insulating layer, and its thickness is controlled at 10-20 microns, which further enhances the stability and durability of the structure. This design is particularly suitable for high-frequency application environments and can achieve high-performance inductors in a compact space.
[0020] Preferably, the method further includes forming a through hole penetrating the copper column and the blue adhesive sheet to achieve electrical connection between the layers.
[0021] By adopting the above technical solution, the through-holes formed through the copper pillars and the blue adhesive sheet can not only ensure stable electrical connection between the layers, but also significantly improve the overall performance and reliability of the micro-inductor. This design allows the current to flow smoothly between different layers, reducing resistance and electromagnetic interference, thereby improving the working efficiency of the inductor and the quality of signal transmission. At the same time, the structure can also effectively prevent damage caused by local overheating and extend the service life of the inductor.
[0022] Preferably, the through hole is filled with electroplating material to achieve vertical conduction between layers. By adopting the above technical solution, the electroplating material filled in the through hole can effectively achieve vertical conduction between layers, ensure the smooth flow of current in the multi-layer structure, and improve the overall performance and reliability of the micro-inductor. At the same time, this design can also reduce signal transmission problems caused by poor contact, and further improve the stability and service life of the product.
[0023] Preferably, it further comprises a UV ink layer, wherein the UV ink layer fills the gaps between the copper pillars.
[0024] By adopting the above technical solution, the UV ink layer can expose the coil, thereby improving the alignment accuracy and conduction reliability of the micro-inductor coil.
[0025] In summary, the present application includes at least one of the following beneficial technical effects: 1. Through laser cutting and UV ink impregnation development and exposure processing, high-precision copper column shape preparation is achieved, which significantly improves the alignment accuracy and conduction reliability of the micro inductor coil; 2. The gap between the copper pillars is controlled within the range of 5-15 microns, ensuring the compactness and stability of the coil, thereby improving the overall performance of the micro-inductor; 3. The organic strip is made of polyimide film, which has good heat resistance and mechanical strength, effectively extending the service life of the micro inductor. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a structural schematic diagram of a micro-inductor coil structure assembled on a circuit board in an embodiment of the present application.
[0027] Figure 2 It is a state diagram of step S1 in the embodiment of the present application.
[0028] Figure 3 It is a state diagram of step S2 in the embodiment of the present application.
[0029] Figure 4 It is a state diagram of step S3 in the embodiment of the present application.
[0030] Figure 5 It is a state diagram of step S4 in the embodiment of the present application.
[0031] Figure 6 It is a state diagram of step S6 in the embodiment of the present application.
[0032] Explanation of the reference numerals: 1. Copper column; 2. Blue adhesive sheet; 3. Organic tape; 4. Through hole; 5. UV ink layer; 6. Copper foil. DETAILED DESCRIPTION
[0033] The following will be combined with the attached Figure 1-Figure 6 , the technical solutions in the embodiments of the present invention are clearly and completely described. The described embodiments are only possible technical implementations of the present invention, not all possible implementations. Those skilled in the art can completely combine the embodiments of the present invention to obtain other embodiments without creative work, and these embodiments are also within the scope of protection of the present invention.
[0034] The inventor of this application has found that the existing micro-inductor manufacturing process has many shortcomings, such as difficulty in achieving high-precision and efficient production. To this end, this application mainly adopts the following technical solutions: Reference Figure 1 and Figure 2 , copper foil 6 is coated on the organic tape 3; the required copper pillar 1 shape is cut out on the A and B surfaces by laser; the A and B surfaces are impregnated with insulating UV ink respectively, and then developed and exposed; the A and B surfaces are aligned and pressed together through a blue adhesive sheet; the temporary protective film on the A and B surfaces is removed; a through hole 4 is formed that penetrates the A and B surfaces to achieve electrical connection between the two surfaces; the through hole 4 is filled with electroplating material to complete the upper and lower conduction of the A and B surfaces. This technical solution effectively solves the problems existing in the prior art and achieves the effect of improving production efficiency and product quality. The following is a further detailed description of this application. Embodiment 1: Reference Figure 2 The present application embodiment provides a process for preparing a coil for a micro-inductor, comprising the following steps: S1: Coating the organic tape 3 with a copper foil 6 .
[0035] Specifically, firstly, a suitable organic tape 3 is selected as the base material. Preferably, the organic tape 3 is a polyimide film, because polyimide has good high temperature resistance, corrosion resistance and high mechanical strength, and is suitable for making precision electronic components. Next, a layer of copper foil 6 is covered on the surface of the organic tape 3. The thickness of the copper foil 6 can be adjusted according to actual needs, and a thickness of 10-50 microns is generally recommended. This can provide sufficient conductivity in the subsequent processing while maintaining good flexibility and processability.
[0036] Reference Figure 3 , also includes: S2: Use laser to cut the required copper pillar 1 shape on the A and B surfaces.
[0037] Subsequently, a high-precision laser device is used to cut copper pillars 1 of the desired shape on the organic tape 3 covered with copper foil 6. To ensure the precise spacing between the copper pillars 1, the laser path can be controlled by programming to keep the gap between the copper pillars 1 within the range of 5-15 microns. The thickness of the copper pillars 1 can also be adjusted by laser power and scanning speed to reach 20-500 microns. This process requires strict quality control to avoid material damage due to excessive laser energy or incomplete cutting due to too little laser energy.
[0038] Reference Figure 4 , also includes: S3: The A side and the B side are impregnated with insulating UV ink respectively, and then subjected to development and exposure treatment.
[0039] Next, a layer of insulating UV ink is applied to the cut A side and B side respectively. The selection of UV ink is also very important. It should not only have good insulating properties, but also have the characteristics of fast curing to facilitate subsequent efficient production. After the coating is completed, the A side and B side with UV ink are placed in a UV exposure machine for development and exposure. Through ultraviolet irradiation, the UV ink can be quickly cured to form a stable insulating layer to prevent short circuits between copper pillars 1.
[0040] Reference Figure 5 , also includes: S4: Align side A and side B and press together using the blue adhesive sheet.
[0041] Next, align the A side and B side, where the UV ink has been cured, and then press them together by hot or cold pressing. To ensure the accurate docking of the two sides, a high-precision positioning fixture, such as an optical alignment system, can be used to ensure that the corresponding positions of the A side and the B side are accurate. In addition, appropriate adhesives can be added during the pressing process to enhance the bonding between the two sides and prevent separation during subsequent processing or use.
[0042] S5: Remove the temporary protective films on the A and B surfaces.
[0043] After lamination, the temporary protective films on the A and B sides need to be removed. These protective films are used to prevent contamination and scratches during the previous processing. Now they are no longer needed and can be removed by solvent cleaning or physical peeling. It is important to ensure that the formed structure is not damaged during the removal process, so as not to affect the quality of the final product.
[0044] Reference Figure 6 , also includes: S6: forming a through hole 4 penetrating the A surface and the B surface to achieve electrical connection between the two surfaces.
[0045] Afterwards, through holes 4 are formed on the A and B surfaces by drilling or laser drilling. The positions and number of these through holes 4 need to be carefully designed to ensure effective electrical connection between the layers. The diameter of the through holes 4 is generally tens of microns to hundreds of microns, and the specific size depends on actual needs. In order to avoid roughness or deformation of the edges of the through holes 4, a fine drill bit or a high-energy laser beam can be used for processing.
[0046] S7: Fill the through hole 4 with electroplating material to complete the upper and lower conduction between the A and B surfaces.
[0047] The last step is to fill the through hole 4 with electroplating material, usually a material with good electrical conductivity such as metal nickel or gold. The electroplating process can be carried out by chemical deposition or electrolytic deposition to ensure that the electroplating layer is uniform and firm. After the electroplating is completed, the electroplating quality and contact resistance in the through hole 4 are checked to confirm whether they meet the design requirements. If necessary, multiple electroplating can be performed or bad parts can be repaired to ensure the reliability and stability of the final product.
[0048] In addition, the present application also provides a coil structure for a micro-inductor, characterized in that it includes a copper column 1 with a threaded orientation, a blue adhesive sheet 2, and a UV ink layer 5. Two groups of copper columns 1 are provided, and the two groups of copper columns 1 are respectively located on the front and back sides of the blue adhesive sheet 2. The gap between adjacent copper columns 1 is 5-15 microns, the thickness of the copper column 1 is 20-500 microns, and the thickness of the blue adhesive sheet 2 is 10-20 microns. The structure also includes a through hole 4 formed through the copper column 1 and the blue adhesive sheet 2 to achieve electrical connection between the layers. The through hole 4 is filled with electroplating material to achieve upper and lower conduction between the layers. The UV ink layer 5 fills the gap between the copper columns 1, thereby improving the alignment accuracy and conduction reliability of the micro-inductor coil.
[0049] Embodiment 2: The difference between this embodiment and the above embodiment is that, in the selection of the organic tape 3, in addition to the polyimide film, other types of flexible substrates can also be selected, such as PET (polyethylene terephthalate) film or PI (polyimide) composite material. These substrates also have excellent mechanical properties and temperature resistance, and can meet the application requirements in different environments.
[0050] In addition, the shape and distribution of the copper pillars 1 can be more diverse. For example, they can be designed into spiral, wavy or other special geometric shapes to increase the inductance value or improve the electromagnetic shielding effect. The gap and thickness between the copper pillars 1 can also be adjusted according to specific application scenarios. For example, in high-frequency circuits, smaller gaps and thinner copper pillars 1 can be selected to reduce parasitic effects and signal loss.
[0051] In the process of forming the through hole 4, more advanced laser drilling technology, such as femtosecond laser or ultrafast pulse laser, can be used to obtain the through hole 4 with higher precision and lower heat-affected zone. This helps to further improve the performance and reliability of the product.
[0052] The implementation principle of this embodiment is: By introducing a variety of substrate options and diversified copper pillar 1 designs, the preparation process of the present invention is more flexible and applicable. In particular, some special shapes and distribution methods of the copper pillars 1 can be optimized for specific application scenarios to improve the overall performance of the product. The application of advanced laser drilling technology further improves the accuracy and quality of the through hole 4 and reduces potential defects and failure rates. In general, these improvement measures not only enrich the possibilities of product design, but also provide more technical support for the research and development of high-end electronic equipment.
[0053] Embodiment 3: The difference between this embodiment and the above embodiment is that different types of insulating materials can be used in the selection of insulating UV ink, such as epoxy resin, silicone rubber or polyurethane. These materials have their own advantages and disadvantages and can be selected according to actual needs. For example, epoxy resin has excellent insulation performance and chemical resistance, but may not perform well in certain extreme environments; silicone rubber has excellent temperature resistance and softness, and is more suitable for occasions with large bending and expansion.
[0054] In addition, the thickness and gap of the copper pillar 1 can also be more finely regulated. For example, for high-frequency circuit applications, the thickness and gap of the copper pillar 1 can be reduced to reduce the influence of parasitic capacitance and stray inductance. For high-current applications, the thickness of the copper pillar 1 can be appropriately increased to improve the current carrying capacity.
[0055] In terms of the filling material of the through hole 4, in addition to the commonly used nickel or gold, other conductive materials such as silver or copper alloy can also be tried. These materials have different conductive properties and cost advantages, and can be weighed and selected according to specific needs.
[0056] The implementation principle of this embodiment is: By selecting different types of insulating materials and conductive materials, and refined parameter control, the preparation process of the present invention can better meet the needs of different application scenarios. This is of great significance for improving product performance and reducing costs. Especially in high-frequency circuits and high-current applications, reasonable material selection and technical optimization can significantly improve product reliability and efficiency. These improvement measures have laid a solid foundation for further market expansion and technological innovation.
[0057] Embodiment 4: The difference between this embodiment and the above embodiment is that when the copper foil 6 is coated on the organic strip 3, a preformed copper foil 6 can be used instead of directly coating the strip. This method can simplify the process and improve production efficiency. The preformed copper foil 6 has been strictly tested for quality before leaving the factory to ensure its flatness and uniformity, thereby reducing the risk of subsequent processing.
[0058] In the laser cutting process, dual laser heads can be used to work synchronously, that is, two laser heads can be used at the same station to cut side A and side B respectively. This can not only speed up the cutting speed, but also improve the cutting accuracy and reduce the accumulation of errors. In addition, a real-time monitoring system can be introduced to automatically correct the laser path to ensure that each batch of products can meet the same high quality standards.
[0059] During the formation of the through hole 4, the electrospark perforation technology can be used, which is an efficient micro-machining method, especially suitable for machining hard materials. The advantages of electrospark perforation are fast speed, high precision, and no limitation on material hardness, which is very suitable for the preparation of micro-inductors.
[0060] The implementation principle of this embodiment is as follows: By adopting 6 preformed copper foils and dual laser head synchronous cutting technology, the efficiency and accuracy of the production process are greatly improved. The application of electrospark perforation technology further improves the processing quality of the through hole 4 and ensures the reliability and consistency of the product. These improvement measures not only shorten the production cycle, but also improve the yield rate, bringing significant economic benefits to the enterprise. At the same time, it also leaves a broad space for future technological development.
[0061] Embodiment 5: The difference between this embodiment and the above embodiment is that: in the selection of the organic tape 3, a self-supporting multilayer structure material can be considered, that is, the copper foil 6 is pre-embedded in the organic tape 3. This material can be purchased directly as a finished product without the need for an additional bottom coating process, which greatly simplifies the production process. At the same time, since the copper foil 6 has been fixed in the organic tape 3, the stability and consistency of the copper column 1 can be better guaranteed.
[0062] In the laser cutting process, 3D laser engraving technology can be used, that is, multi-level three-dimensional processing on a plane. This method can complete multiple levels of cutting and forming at one time, greatly improving production efficiency. In addition, a machine vision system can be introduced to monitor deviations in the cutting process in real time and make corrections in time to ensure the accuracy and consistency of each layer.
[0063] During the formation of the through hole 4, nanojet technology can be used, that is, liquid containing conductive particles is sprayed at high speed to achieve uniform filling in the through hole 4. The biggest feature of nanojet technology is that it can be precisely controlled at a very fine scale, avoiding the unevenness and bubble problems that may occur in traditional electroplating methods.
[0064] The implementation principle of this embodiment is: By adopting self-supporting multilayer structural materials and three-dimensional laser engraving technology, the preparation process of the present invention can achieve high integration and automation. In particular, the application of nano-injection technology makes the filling of through hole 4 more uniform and reliable, further improving the performance and life of the product. These innovative measures not only improve the level of intelligent production, but also provide new ideas for future multifunctional integrated design. In general, these improvement measures give the present invention a stronger advantage in market competition.
[0065] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A process for preparing a coil for a micro-inductor, characterized in that: The following steps are involved: S1: coating the organic tape (3) with a copper foil (6); S2: Use laser to cut the required copper pillar (1) shape on the A and B surfaces; S3: impregnating the A side and the B side with insulating UV ink respectively, and performing development and exposure treatment; S4: Align surface A and surface B and press them together using the blue adhesive sheet; S5: removing the temporary protective film on the A surface and the B surface; S6: forming a through hole (4) penetrating the A surface and the B surface to achieve electrical connection between the two surfaces; S7: Fill the through hole (4) with electroplating material to complete the upper and lower conduction between the A and B surfaces.
2. The process for preparing a coil for a micro-inductor according to claim 1, characterized in that: The gap between the copper pillars (1) is 5-15 microns.
3. The process for preparing a coil for a micro-inductor according to claim 1, characterized in that: The thickness of the copper column (1) is 20-500 microns.
4. The process for preparing a coil for a micro-inductor according to claim 1, characterized in that: The thickness of the blue adhesive sheet (2) is 10-20 microns.
5. The process for preparing a coil for a micro-inductor according to claim 1, characterized in that: The thickness of the copper foil (6) is 10-50 microns.
6. The process for preparing a coil for a micro-inductor according to claim 1, characterized in that: The organic tape (3) is made of polyimide film.
7. A coil structure for a micro-inductor, manufactured by the micro-inductor coil manufacturing process according to claims 1-6, characterized in that: It comprises a plurality of copper pillars (1) and a blue adhesive sheet (2) in a spiral orientation, wherein the gap between adjacent copper pillars (1) is 5-15 microns, the thickness of the copper pillars (1) is 20-500 microns, and the thickness of the blue adhesive sheet (2) is 10-20 microns.
8. The process for preparing a coil for a micro-inductor according to claim 7, characterized in that: The method also includes forming a through hole (4) penetrating the copper column (1) and the blue adhesive sheet (2) to achieve electrical connection between the layers.
9. The process for preparing a coil for a micro-inductor according to claim 7, characterized in that: The through hole (4) is filled with electroplating material to achieve vertical conduction between layers.
10. The process for preparing a coil for a micro-inductor according to claim 7, characterized in that: It also comprises a UV ink layer (5), wherein the UV ink layer (5) fills the gaps between the copper pillars (1).
Citation Information
Patent Citations
Processing method and processing system of circuit board
CN110035617A
Manufacturing method of high-performance film inductance coil
CN119181584A
Inductance coil
CN203325659U
Printed circuit and its manufacture
JP1997260810A
Manufacturing Process Of Printed Circuit Board ForDouble Side HCCL
KR1020060088144A